Myopia control effect of defocus incorporated multiple segments (DIMS) spectacle lens in Chinese children: results of a 3-year follow-up study. Issue 8 (17th March 2021) - Lam, Carly SY; Tang, Wing Chun; Lee, Paul H; Zhang, Han Yu; Qi, Hua; Hasegawa, Keigo; To, Chi Ho
Abstract : Aims: To determine myopia progression in children who continued to wear the defocus incorporated multiple segments (DIMS) lenses or switched from single vision (SV) to DIMS lenses for a 1-year period following a 2-year myopia control trial. Methods: 128 children participated in this study. The children who had worn DIMS lenses continued to wear DIMS lenses (DIMS group), and children who had worn SV lenses switched to wear DIMS lenses (Control-to-DIMS group). Cycloplegic spherical equivalent refraction (SER) and axial length (AL) were measured at 6-month interval. Historical controls were age matched to the DIMS group at 24 months and used for comparing the third-year changes. Results: Over 3 years, SER and AL changes in the DIMS group (n=65) were −0.52±0.69D and 0.31±0.26 mm; these changes were not statistically significant over time (repeated measures analysis of variance, p>0.05). SER (−0.04±0. 38D) and AL (0.08±0.12 mm) changes in the Control-to-DIMS group (n=55) in the third year were less compared with the first (mean difference=0.45 ± 0.30D, 0.21±0.11 mm, p<0.001) and second (0.34±0.30D, 0.12±0.10 mm, p<0.001) years. Changes in SER and AL in both groups over that period were significantly less than in the historical control group (DIMS vs historical control: mean difference=−0.18±0.42D, p=0.012; 0.08±0.15 mm, p=0.001; Control-to-DIMS versus historical control: adjusted mean differences=−0.30±0.42D, p<0.001; 0.12±0.16 mm, p<0.001). Conclusions: Myopia control effect was sustained in the third year in children who had used the DIMS spectacles in the previous 2 years and was also shown in the children switching from SV to DIMS lenses.